Molecular detection of parasites and host preference in wild-caught Culicoides biting midges (Diptera: Ceratopogonidae) in Chiang Mai and Nakhon Si Thammarat Provinces, Thailand - Kyi Soe Baby; Kaewmee Saowalak; Mano Chonlada; Pattanawong Urassaya; Tipparawong Nopporn; Siriyasatien Padet; Gatherer Derek; Urbaniak Michael D.; Bates Paul A.; Jariyapan Narissara (Parasite)
Culicoides biting midges (Diptera: Ceratopogonidae) have been reported as potential vectors for haemoparasites. Information about host-vector-parasite specificity is required to confirm their status. Here, molecular detection of haemosporidians, Leishmania, trypanosomatids, and filarial nematodes in biting midges was conducted to understand their potential role as vectors, and their host preference was determined. Wild-caught biting midges were collected from six different localities of Chiang Mai and Nakhon Si Thammarat provinces, Thailand. A total of 6,578 individual Culicoides (170 males, 6,408 females) comprising 15 species of six sub-genera and two groups were collected. Also, 738 parous females and 29 engorged females were examined for parasites and host blood meals, respectively. Culicoides arakawae, C. mahasarakhamense, C. peregrinus and C. innoxius in Chiang Mai province, and C. innoxius and C. peregrinus in Nakhon Si Thammarat province were the most dominant species. Leucocytozoon spp., Leucocytozoon caulleryi and Plasmodium juxtanucleare were identified in five Culicoides species including C. mahasarakhamense, C. arakawae, C. oxystoma, C. fulvus, and C. guttifer. This study is the first record of L. caulleryi in the biting midge C. arakawae in Thailand. Blood meal analysis revealed that Culicoides primarily fed on cattle (17/29, 58.6%), followed by chickens (10/29, 34.5%), and humans (2/29, 6.9%). Our findings confirmed the existence of several Culicoides species in Thailand, which might be potential vectors for transmission of haemosporidians (Leucocytozoon and Plasmodium). Information from host blood meal analyses underlined their preference for large mammals, followed by domestic chickens. More anthropophilic Culicoides species remain to be discovered.